2012
DOI: 10.2355/isijinternational.52.342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Structural Properties of Calcium Aluminosilicate Slags with Varying Al2O3/SiO2 Ratios

Abstract: Molecular dynamics simulation was explored to investigate the change of structure of calcium aluminosilicate slags with varying Al2O3/SiO2 ratios at a fixed CaO content. In practice the results of the study are relevant to the significant changes in slag structure caused by the changes in chemical composition during continuous casting of steels containing high amounts of dissolved aluminum. It was found that Q 4 tetrahedral species (tetrahedron with four bridging oxygens) increase while NBOs (non-bridging oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 32 publications
10
56
0
Order By: Relevance
“…The values of Si-O, Al-O, Ti-O and Ca-O are 1.6, 1.75, 1.9 and 2.3 Å, respectively. The bond length of Si-O, Al-O, Ti-O and Ca-O are in accordance with previous results although in different slag systems, 24,25,29,31) indicating that the strong stability of shortrange order less than 6 Å despite of different systems. The combining capacity between cations and O 2-were also presented by comparing the bond length and it can be obviously seen that the rank of stability is Si-O > Al-O > Ti-O > Ca-O, which is opposite to the rank of their lengths.…”
Section: Pair Distribution Function and Coordinationsupporting
confidence: 80%
See 2 more Smart Citations
“…The values of Si-O, Al-O, Ti-O and Ca-O are 1.6, 1.75, 1.9 and 2.3 Å, respectively. The bond length of Si-O, Al-O, Ti-O and Ca-O are in accordance with previous results although in different slag systems, 24,25,29,31) indicating that the strong stability of shortrange order less than 6 Å despite of different systems. The combining capacity between cations and O 2-were also presented by comparing the bond length and it can be obviously seen that the rank of stability is Si-O > Al-O > Ti-O > Ca-O, which is opposite to the rank of their lengths.…”
Section: Pair Distribution Function and Coordinationsupporting
confidence: 80%
“…The second item on the right hand denotes the short-range repulsion interaction between two atoms which are determined by parameters of Bij and Rij. The parameters were adopted from Zheng's work 25) as well as our previous study 26) to insure the accuracy. The parameters Bij and Rij, corresponding to the short-range repulsion interaction between two atoms, were listed in Table 1.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,22) However, in this CaO-P 2 O 5 -SiO 2 slag system, oxygen tricluster was not found, this is probably because the content of CaO is high, which increases the difficulty of forming complicated clusters and anions. The distributions of the BO, NBO and O 2¹ are presented in Fig.…”
Section: The Partial Radial Distribution Function (Rdf) and Coordinatmentioning
confidence: 89%
“…Zheng et al confirmed this microstructural modification of the CaOAl2O3-SiO2 system with composition variation using Molecular Dynamics simulation. 51) This found that although the SiO4 network may be depolymerized by initial Al2O3 addition, Si and Al are likely to subsequently coordinate together to form a new network cluster. By careful analyses of the microstructure of molten slags, the amphoteric behavior could be clearly understood and an interrelationship among the thermophysical properties of the molten silicate was verified.…”
Section: )mentioning
confidence: 99%